PENGARUH ARANG SEKAM DAN BOKASHI JERAMI PADI TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) - Alfionita, Alfionita; Kadekoh, Indrianto; Syamsiar, Syamsiar (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study, conducted in Poboya Village, Tanamodindi, South Palu, from January to April 2022, investigated the effects of rice husk charcoal and rice straw bokashi on the growth and yield of peanut (Arachis hypogaea L.). A Randomized Block Design (RBD) with a factorial arrangement was used, involving two factors: rice husk charcoal (0, 2, 4, and 6 kg/plot) and rice straw bokashi fertilizer (0, 2, 4, and 6 kg/plot). Each treatment was replicated three times. Observations included plant height, number of leaves, number of branches, flowering age (days), number of pods, pod weight, dry pod weight, and weight of 100 seeds. The results indicated that both rice husk charcoal and rice straw bokashi, each at a dose of 15 t/ha, significantly enhanced the growth and yield of peanut plants. However, no significant interaction was observed between rice husk charcoal and rice straw bokashi on the growth and yield parameters of peanuts.